2014
DOI: 10.1242/jcs.152728
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic trafficking of laminin is controlled by dystroglycan and disrupted in cancers

Abstract: The dynamic interactions between cells and basement membranes serve as essential regulators of tissue architecture and function in metazoans, and perturbation of these interactions contributes to the progression of a wide range of human diseases, including cancers. Here, we reveal the pathway and mechanism for the endocytic trafficking of a prominent basement membrane protein, laminin-111 (referred to here as laminin), and their disruption in disease. Livecell imaging of epithelial cells revealed pronounced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Recent studies in human epithelial cells demonstrated that DG can mediate the endocytosis of its natural ligand, the ECM protein laminin, via a dynamin-dependent pathway (61). Notably, the internalization of laminin was followed by rapid delivery to late endosomes with kinetics similar to those of DG-mediated viral entry observed here.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Recent studies in human epithelial cells demonstrated that DG can mediate the endocytosis of its natural ligand, the ECM protein laminin, via a dynamin-dependent pathway (61). Notably, the internalization of laminin was followed by rapid delivery to late endosomes with kinetics similar to those of DG-mediated viral entry observed here.…”
Section: Resultssupporting
confidence: 74%
“…2J). In sum, our data suggested that rLCMV-LASVGP entry via DG involves a macropinocytosis-related pathway different from the DG-mediated endocytosis of laminin (61).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…We show that laminin, an easily accessible extracellular protein, is endocytosed and internalized into lysosomes, providing a source of EAAs that support starved epithelial cell survival. Although laminin endocytosis has previously been reported27, this process involved a distinct receptor and occurred in a different tissue context not linked to metabolism or starvation. Our study shows instead that ITGB4-mediated laminin internalization occurs under conditions of decreased PI3K/mTOR signalling, which mimic loss of nutrient uptake.…”
Section: Discussionmentioning
confidence: 90%